2020
DOI: 10.1371/journal.pgen.1008185
|View full text |Cite
|
Sign up to set email alerts
|

A cross-disorder PRS-pheWAS of 5 major psychiatric disorders in UK Biobank

Abstract: Psychiatric disorders are highly heritable and associated with a wide variety of social adversity and physical health problems. Using genetic liability (rather than phenotypic measures of disease) as a proxy for psychiatric disease risk can be a useful alternative for research questions that would traditionally require large cohort studies with long-term follow up. Here we conducted a hypothesis-free phenome-wide association study in about 330,000 participants from the UK Biobank to examine associations of pol… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
48
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 63 publications
(55 citation statements)
references
References 57 publications
7
48
0
Order By: Relevance
“…Associations with measures of SLEs were seen with several of the disorders. These results are in line with a previous study reporting that the PRSs for five major psychiatric disorders are associated with mental health‐related traits in adult life in the general population; more specifically, the PRSs for ADHD, MDD, and SCZ have been found associated with trauma‐related phenotypes (Leppert et al, 2020 ). MDD was the only disorder, which was related both to ADHD symptoms and to SLEs.…”
Section: Discussionsupporting
confidence: 92%
“…Associations with measures of SLEs were seen with several of the disorders. These results are in line with a previous study reporting that the PRSs for five major psychiatric disorders are associated with mental health‐related traits in adult life in the general population; more specifically, the PRSs for ADHD, MDD, and SCZ have been found associated with trauma‐related phenotypes (Leppert et al, 2020 ). MDD was the only disorder, which was related both to ADHD symptoms and to SLEs.…”
Section: Discussionsupporting
confidence: 92%
“…ADHD symptoms tend to persist into adulthood in 65% of children diagnosed with the condition ( 3 ). Even when ADHD symptoms do not persist into adulthood, childhood ADHD symptoms can potentially have long-lasting effects on physical health later in life ( 51 ).…”
Section: Discussionmentioning
confidence: 99%
“…PheWAS typically associates a genetic variant ( ) with hundreds of disease codes ( ) with association models of the structure . Due to computational advances and development of widely available analytic frameworks [ 2 , 3 , 4 , 5 , 6 ], PheWAS is now relatively easy to implement. The main goal of a PheWAS is to replicate known gene–disease relationships and to search for hidden and unanticipated associations (for example, Li et al found that there is a strong negative association between the tag single nucleotide polymorphism (SNP) for blood group O antigen and arm impedance) [ 2 , 7 , 8 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%